Respuesta :
Take the square root of each side of the equation to set-up the solution (x−3)2⋅12=±√49x-32⋅12=±49
Remove the perfect root factor x−3x-3 under the radical to solve for xx.(x−3)=±√49x-3=±49Simplify
(x−3)=±7x-3=±7The complete solution is the result of both the positive and negative portions of the solution.
ANSWER : x=10,−4
Remove the perfect root factor x−3x-3 under the radical to solve for xx.(x−3)=±√49x-3=±49Simplify
(x−3)=±7x-3=±7The complete solution is the result of both the positive and negative portions of the solution.
ANSWER : x=10,−4
(x-3)² = 49
x-3 = ±√49
х-3=-7 or x-3=7
x=-7+3 x=7+3
x₁=-4 x₂=10
Answer: x=-4; x=10
x-3 = ±√49
х-3=-7 or x-3=7
x=-7+3 x=7+3
x₁=-4 x₂=10
Answer: x=-4; x=10